A Field-based Review of the ICT Utilization in the Banking Sector the Case of the Commercial Banks in Oman - Tareq Alhousary; Jason Underwood; Dimitrios Xanthidis (New Innovations in Economics, Business and Management Vol. 2, 2021)
At present, the discourse on how vital the role of technology, the information and communication technology (ICT) in particular, in business is just over. Today’s research focus has been already shifted to fine tune the utilization of ICT and measure its role in achieving the strategic business goals. This is evident by the literature focusing on narrow scopes of businesses to provide better ICT calibration in terms of utilization and contribution to business system as a whole. This study aims at contributing to advancing the role of ICT in realizing the business strategic goals. The banking sector was selected to explore how advanced is its utilization of its ICT resources. Oman was taken as a sample from the Gulf-Cooperation Council (GCC) countries. The mixed methodology, qualitative and quantitative, had been selected and data collection tools comprised of a self-administered questionnaire and an interview. The descriptive statistics were used using SPSS 16. The interviews were used for data triangulation as well as for getting deeper insights and help explaining the quantitative data. The study results show that the selected sector has adopted latest ICT infrastructure in conducting both back- and front-office business processes. However, the study finds that while ICT resource is readily available in this sector, there is still scope for improvement on its management side.